INTERNAL CONTROL DAN HUBUNGANNYA DENGAN EARNINGS MANAGEMENT - Makhdalena , (Media Riset Bisnis & Manajemen, 2012)
Manipulation of accounting (earnings management) that occurs causes the collapse of the giant corporations of the world in the early 2000s and has hurt the company's stakeholders. Manipulation of accounting also occurs in companies listed on the Jakarta Stock Exchange. The occurrence of accounting manipulation makes accounting experts to focus on internal control problems because of internal control is an important issue that affects earnings management through a substance that can be provided by an internal control. Based on such consideration, the researcher is interested in doing research that aims to determine the correlation of internal control on earnings management. Research done by the manufacturing survey at 48 listed companies in Jakarta Stock Exchange drawn at random in a population of 150 firms. The data used in this study is the primary data for the internal control variable and secondary data for earnings management variable. Data were analyzed using Product Moment. The results showed that the internal control was significantly negatively related to earnings management.Keywords: Internal control, Earnings management